A case report of placenta fenestrate - Firouze Ziaee; Fatemeh Zahra karimi; Masoumeh Mirteimouri; Elaheh Mansouri Ghezel Hesari (Mashhad University of Medical Sciences, 2021)
Introduction: One of the variants of the placenta is the placenta fenestrate. In rare cases, the central part of the placental disc is missing. In some cases, there is a real hole in the placenta. A porous placenta may be mistaken for a placental cotyledon after delivery. In the present study, a case of placenta fenestrate was reported. Case presentation: The patient was 31year old woman, G3L2, with a gestational age of 39 weeks who had complained of labor pains and referred to the emergency department of Hazrat Umm Al-Banin Gynecology Hospital. Following a normal delivery, the baby girl was born with Apgar 9-10, weighing 3780 gr and seemingly healthy. Spontaneous departure of the placenta occurred 15 minutes after birth. On examination of the placenta, the placenta was a discoid plate in the center of which there was no part of the cotyledon in the form of a hole 3 cm in diameter, complete placental membranes covered the entire surface of the placenta, and the umbilical cord was connected to the placenta as a marginal joint. Conclusion: Familiarity with a fenestrate placenta can help prevent mistake in postpartum examinations. Therefore, it is recommended to pay attention to the characteristics of different types of placenta in postpartum examination.